Multi-layer solar interface evaporator and preparation method and application thereof

By composite biomass and polymer materials to prepare a multilayer solar interface evaporator, the problems of salt precipitation and weak binding force of the evaporator in high-salt environments are solved, and efficient photothermal conversion and pollutant adsorption are achieved, which is suitable for seawater desalination and industrial wastewater treatment.

CN120794067APending Publication Date: 2025-10-17CHENGDU UNIV

Patent Information

Application Number
CN202510890520.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing multi-layer solar interface evaporators are prone to precipitating salt crystals in high-salt environments, resulting in pore blockage and a decrease in evaporation rate, weak interlayer bonding, low water transfer efficiency, and large heat loss.

Method used

Carbonized loofah powder is combined with polyacrylonitrile fiber membrane to form an in-situ grown polyaniline photothermal layer. Loofah is used as the connecting layer, and polyamide 6-bamboo charcoal powder foam is used as the supporting layer. The multilayer structure is prepared by electrospinning and solution foaming technology to enhance the interlayer bonding force and optimize the water transmission path, thereby blocking the photothermal layer from contact with high-salt solution.

Benefits of technology

It achieves efficient light-to-heat conversion and pollutant adsorption, reduces salt crystal precipitation, increases evaporation rate and service life, and is suitable for seawater desalination and industrial wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120794067A_ABST
    Figure CN120794067A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer composite materials, and relates to a multilayer solar interface evaporator and a preparation method thereof. The evaporator comprises a photo-thermal layer, a connecting layer and a supporting layer, the photo-thermal layer combines biomass material-carbonized loofah powder with high polymer material polyacrylonitrile, a photo-thermal film with photo-thermal conversion capacity is prepared through the electrostatic spinning technology, and polyaniline grows on the surface of the photo-thermal film in situ so as to improve the photo-thermal efficiency; the connecting layer adopts a loofah sponge fiber skeleton, so that the layers are tightly combined; the supporting layer selects polyamide 6 as a foaming material and bamboo charcoal powder as a functional filler, and the polyamide 6-bamboo charcoal powder foam supporting layer is prepared by utilizing a solution foaming technology and has the functions of heat insulation, water delivery and dye adsorption. The photo-thermal layer and the supporting layer are integrated through the connecting layer to prepare the multi-layer solar interface evaporator, efficient photo-thermal evaporation, high dye adsorption rate and long cycle life are achieved, and the multi-layer solar interface evaporator has the advantages of being environmentally friendly, low in cost and stable in performance and has application prospects in the fields of seawater desalination and industrial wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of polymer composites, and particularly relates to a multi-layer solar interfacial evaporator with efficient light-heat conversion and pollutant adsorption functions and a preparation method thereof, which is suitable for seawater desalination, industrial wastewater treatment and the like. BACKGROUND

[0002] Solar-driven interfacial evaporation technology has become an important direction for solving global freshwater resource shortage due to its low energy consumption and environmental friendliness. A typical multi-layer interfacial evaporator is composed of a photo-thermal layer and a support layer. The photo-thermal layer is responsible for absorbing light energy and converting it into heat energy, and the support layer is used for heat management, water transport and structural support.

[0003] In the development process of the photo-thermal layer, natural biomass materials have gradually become ideal candidates due to their wide sources, porous structures and light-heat conversion capabilities. For example, a wax gourd has a unique inner-outer anisotropic structure. The outer wax gourd skin is dense and tough, and the inner wax gourd pulp is porous and hydrophilic. After freeze-drying and carbonization treatment, the wax gourd can retain excellent structural stability and light-heat performance. However, single biomass materials have limited evaporation area and are not easy to modify, so they need to be combined with polymer materials to expand their functions. Therefore, carbonized wax gourd powder is combined with polyacrylonitrile (PAN) to prepare CL-PAN fiber membranes with light-heat conversion performance using electrospinning technology. Polyaniline (PANI) is further grown in situ to further improve the light-heat conversion capability, which can significantly improve the performance limitations of single materials.

[0004] In the development process of the support layer, polymer foams have become an important direction due to their lightweight floating, heat insulation and hydrophilic properties. For example, polyamide 6 (PA6) foam can be prepared by solution foaming technology. By introducing bamboo charcoal powder (BC) into the foaming solution, PA6-BC modified foam can be prepared, which can also endow the support layer with the function of adsorbing pollutants such as dyes. The current combination method of the photo-thermal layer and the support layer has obvious defects. They are simply stacked, and the interlayer bonding force is weak, which not only leads to low water transport efficiency, but also causes large heat loss. At the same time, in a high-salt environment, salt crystals are easily precipitated on the surface of the photo-thermal layer, blocking the pores, which significantly reduces the evaporation rate and service life. SUMMARY

[0005] Therefore, the present application discloses a multi-layer solar interfacial evaporator and a preparation method thereof. The multi-layer solar interfacial evaporator is a structure-stable and function-integrated multi-layer solar interfacial evaporator. By combining biomass materials with polymer materials, an integrated multi-layer structure with efficient light-heat conversion and pollutant adsorption functions is constructed, which solves the deficiencies of existing evaporators in complex water quality treatment.

[0006] It should be noted that the loofah sponge connecting layer adopted in the present application closely links the light-heat layer and the supporting layer through its network structure, enhances the interlayer bonding force while optimizing the water transport path and reducing heat loss, and can effectively reduce the precipitation of salt crystals on the surface of the light-heat layer and the pore blockage through the blocking of the direct contact of the light-heat layer with the high-salt solution and the adsorption of the supporting layer.

[0007] In order to achieve the above-mentioned purpose, the present application provides the following technical scheme:

[0008] The first technical purpose of the present application is to provide a whole structure of a multilayer solar interface evaporator, which is specifically as follows:

[0009] The light-heat layer is formed by in-situ growth of polyaniline (PANI) on the surface of carbonized loofah (CL) powder and polyacrylonitrile (PAN) fiber membrane as a substrate, forming a carbonized loofah-polyacrylonitrile-polyaniline (CL-PAN-PANI) light-heat layer. The carbonized loofah powder is obtained by carbonizing fresh loofah after freeze-drying at 400-800℃ (preferably 500℃), and has a porous structure and a high specific surface area; the PAN fiber membrane is prepared by electrospinning, providing a high specific surface area fiber carrier; PANI is a typical polymer with light-heat function, which is loaded on the surface of the fiber through in-situ polymerization, enhancing the light-heat conversion efficiency.

[0010] The connecting layer adopts a loofah fiber skeleton, which has a natural porous fiber structure as the connecting layer, with the fiber light-heat layer attached to the upper surface and the foam supporting layer embedded in the lower surface, realizing the combination of the light-heat layer and the supporting layer, avoiding the damage of the light-heat layer during the foaming process of the supporting layer, and providing a water transport channel between the two layers.

[0011] The supporting layer is a polyamide 6-bamboo charcoal powder (PA6-BC) foam, which is prepared by a solution foaming technology. The PA6 foam has the characteristics of light weight, low thermal conductivity and porous structure, and the addition of bamboo charcoal powder (BC) (mass ratio of 1%-4%, preferably 3%) endows it with dye adsorption capacity, and optimizes the pore structure to improve the water transport efficiency.

[0012] The second technical purpose of the present application is to provide a preparation method of the multilayer solar interface evaporator as described above, which specifically includes the following steps:

[0013] Step (1) Preparation of photothermal layer (CL-PAN-PANI) / connection layer (loofah): PAN powder and CL powder are dissolved in N,N-dimethylformamide (DMF) in a corresponding mass ratio, and a uniformly dispersed spinning solution is obtained after sufficient stirring and ultrasonic dispersion; the spinning solution is loaded into a syringe and spun on the surface of the loofah connection layer to obtain a CL-PAN fiber membrane; the CL-PAN membrane is immersed in a dilute hydrochloric acid solution, and aniline and ammonium persulfate in corresponding proportions are added. After stirring in an ice-water bath, PANI is induced to polymerize in situ on the fiber surface. After rinsing with deionized water and drying, CL-PAN-PANI / loofah is obtained. The CL-PAN-PANI fiber membrane attached to the upper surface of the loofah connection layer is the photothermal layer.

[0014] Step (2) Preparation of the support layer (PA6-BC foam): PA6 particles are dissolved in formic acid (FA), bamboo charcoal powder (BC) is added, and magnetic stirring is performed until a black uniform solution is obtained to obtain a PA6 / formic acid / BC solution; the PA6 / formic acid / BC solution is poured into a mold, and a sodium carbonate aqueous solution is added dropwise to induce phase separation and bubble formation. After standing and solidifying, the mixture is rinsed with deionized water three times and dried in an oven to obtain a lightweight porous PA6-BC foam.

[0015] Step (3) integrated assembly preparation: immerse the CL-PAN-PANI / loofah in the PA6-BC foaming solution, induce the foaming reaction through the sodium carbonate solution, so that the foam layer is tightly combined with the loofah fiber skeleton to form an integrated structure of the photothermal layer-connection layer-support layer.

[0016] Preferably, in step (1), the spinning solution is prepared by dissolving PAN powder and CL powder in N,N-dimethylformamide (DMF) at a mass ratio of 1:1, wherein the PAN concentration is 10 wt%, stirring for 5 h and then ultrasonically dispersing for 30 min to obtain a uniformly dispersed spinning solution; electrospinning: the spinning solution is loaded into a syringe, and the voltage is set to 18-22 kV (preferably 20 kV) and the pushing speed is 0.0008-0.001 mm / s (preferably 0.0008 mm / s ), the distance between the needle tip and the receiver is 15 cm, spinning on the surface of the loofah for 6-12 hours (preferably 6 hours), and drying at 60°C for 6 hours to obtain a CL-PAN fiber membrane; PANI in situ growth: the CL-PAN fiber membrane was immersed in a 1 mol / L hydrochloric acid solution, aniline and ammonium persulfate (initiator, with a molar ratio of 1:1 to aniline) were added, and stirred in an ice-water bath for 6 hours to induce in situ polymerization of PANI on the fiber surface. After rinsing with deionized water, the fiber was dried in an oven at a constant temperature of 80°C for 12 hours.

[0017] Preferably, in step (2), the support layer preparation (PA6-BC foam) is prepared: foam solution preparation: PA6 particles are dissolved in a 16% mass fraction formic acid solution, 1%-4% (preferably 3%) of 400 mesh bamboo charcoal powder is added, and magnetic stirring is performed until a black viscous uniform solution is obtained; solution foaming: the PA6 / formic acid / BC solution is poured into a mold, sodium carbonate aqueous solution is added dropwise to react with formic acid to generate CO2, phase separation and bubble generation are induced, and after solidification, the product is washed with deionized water three times and dried in an oven at 60°C.

[0018] Preferably, in step (3), the CL-PAN-PANI / loofah prepared in step (1) is cut into a size slightly smaller than the mold, and placed in the mold with the photo-thermal layer on top and the connecting layer on the bottom. A syringe is used to slowly inject the sodium carbonate-containing aqueous solution into the mold containing the PA6-BC foaming solution through the edge gap. After all the sodium carbonate aqueous solution is added, the product is allowed to solidify, removed with tweezers, washed with deionized water three times, and dried in an oven at 60°C for 12 hours.

[0019] It should be noted that the additional foam support layer not only supports the photo-thermal part to prevent the photo-thermal layer from directly contacting the water surface and causing damage, but also provides additional water transport channels inside the support layer to slowly and evenly wet the surface of the photo-thermal layer. In addition, the support layer also has the effect of preventing heat loss.

[0020] A third technical object of the present application is to provide a multi-layer solar interface evaporator for seawater desalination.

[0021] Compared with the prior art, the multi-layer solar interface evaporator and its preparation method and application provided by the present application have the following innovative points:

[0022] (1) Biomass-polymer composite photo-thermal layer: the porous structure of carbonized loofah and the high specific surface area of PAN fiber membrane provide abundant attachment sites and abundant water transport channels for PANI; the in-situ growth of PANI enhances light absorption and thermal conductivity, achieving efficient photo-thermal conversion.

[0023] (2) Functional foam support layer: the heat insulation of PA6 foam and the adsorption of bamboo charcoal powder are synergistic, not only providing stable support and water transport channels, but also effectively removing organic pollutants such as dyes.

[0024] (3) Natural connecting layer strengthens the interface bonding: the natural fiber skeleton of loofah can be combined with the adhesive nanofiber to serve as a transition layer, which can avoid the problem of interlayer separation in traditional stacked structures.

[0025] Through the above technical solutions, compared with the prior art, the multi-layer solar interface evaporator and its preparation method and application provided by the present application have the following excellent effects:

[0026] 1) The multilayered interfacial evaporator fabricated by this invention utilizes solar-powered interfacial evaporation and filtration and adsorption, demonstrating excellent water treatment capabilities. During the treatment of pollutant-laden seawater, it simultaneously removes pollutants while evaporating and purifying the seawater, ensuring high wastewater treatment efficiency and long-term performance. This multilayered solar interfacial evaporator has promising application prospects in seawater desalination and industrial wastewater treatment.

[0027] 2) The multi-layer interface evaporator prepared by the present invention has a good evaporation rate: under the intensity of 1 sun, the evaporation rate of fresh water reaches 1.799 kg m -2 h - 1. Brine (3.5 wt.% NaCl) evaporation rate 1.675 kg m -2 h - 1. Superior to most biomass-based evaporators; Excellent salt tolerance: The loofah sponge connecting layer and the foam support layer work together to reduce the direct contact of the photothermal layer with salt water. After 5 hours of continuous irradiation, there is no obvious salt deposition on the surface of the photothermal layer, and the evaporation rate is stable; High organic dye pollutant removal ability: The adsorption rate of PA6-BC foam for methylene blue dye reaches 96.9%. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0029] Figure 1 Schematic diagram of the microstructure of PAN(ab), CL-PAN(cd), and CL-PAN-PANI(ef).

[0030] Figure 2 These are the microstructures of foam support layers containing 0 wt.% (a), 1 wt.% (b), 2 wt.% (c), 3 wt.% (d), and 4 wt.% (e) BC.

[0031] Figure 3 Salt deposition of CL-PAN, CL-PAN-PANI, and multilayer solar interface evaporator under 5h light irradiation and brine (3.5wt.%) conditions.

[0032] Figure 4 Graph showing the water evaporation efficiency of a multilayer solar interface evaporator in pure water and salt water (3.5 wt. %) for ten cycles of water evaporation.

[0033] Figure 5 is a graph of the adsorption of the multilayer solar evaporator in a 10 mg / L methylene blue solution for 5 h. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the present application.

[0035] Herein, the special word "embodiment" as "exemplary" explained any embodiment does not have to be interpreted as superior or better than other embodiments. In the performance index test of the embodiments of the present application, unless otherwise specified, the conventional test method in the art is adopted. It should be understood that the terms described in the present application are only for describing the specific embodiments, and are not used to limit the disclosure of the present application.

[0036] Unless otherwise specified, the technical and scientific terms used herein have the same meanings as generally understood by those skilled in the art to which the present application belongs; as the test methods and technical means not specially noted in the present application are all the experimental methods and technical means generally used by those skilled in the art.

[0037] In order to better illustrate the content of the present application, a large number of specific details are given in the specific embodiments below. Those skilled in the art should understand that the present application can also be implemented without some specific details. In the embodiments, some methods, means, instruments, equipment and the like which are well known to those skilled in the art are not described in detail, in order to highlight the main idea of the present application.

[0038] The technical features disclosed in the embodiments of the present application can be combined in any way without conflict, and the technical solutions obtained by combination belong to the disclosure of the embodiments of the present application.

[0039] The embodiments of the present application disclose a preparation method of a multilayer interface evaporator based on lagenaria biomass.

[0040] In order to better understand the present application, the following embodiments are further specifically described, but it should not be understood as limiting the present application. Some non-essential improvements and adjustments made by those skilled in the art according to the above disclosure are also regarded as falling within the protection scope of the present application.

[0041] Embodiment 1

[0042] The preparation of the CL-PAN-PANI photothermal layer is as follows:

[0043] Take 0.5 g CL-500 powder and 0.5 g PAN powder, add 6 mL DMF, heat and magnetic stir until PAN is completely dissolved, ultrasonic dispersion for 30 min to make CL powder uniformly dispersed, then stir on the magnetic stirrer for 5 h for standby; then, the spinning solution is loaded into a 10 mL syringe, and the voltage is set to 20 kV, the pushing speed is 0.0008 mm / s, the receiver is a drum wrapped with loofah, the spinning time is 6 h, and after collection, it is dried in a 60°C oven for 6 h to obtain a CL-PAN fiber membrane; then, 50 mL of 1 mol / L hydrochloric acid solution is prepared, 0.457 mL of aniline (0.005 mol) is added, and after ultrasonic mixing, it is placed in an ice water bath. Take 1.141 g of ammonium persulfate (0.005 mol) and dissolve it in the remaining hydrochloric acid solution, add the aniline solution dropwise, continue to stir for 6 h, take out the membrane, rinse it with deionized water 3 times, and dry it at 80°C for 12 h to obtain a light-heat layer uniformly loaded with PANI.

[0044] Example 2:

[0045] The preparation of PA6-BC foam support layer (3 wt.% bamboo charcoal powder) is as follows:

[0046] Take 4.67 g of PA6 particles and add 20 mL of formic acid. Stir magnetically until completely dissolved to form a 16 wt.% PA6 / formic acid solution. Add 3 wt.% of 400 mesh bamboo charcoal powder and continue stirring for 1 h until uniform. Then, pour 20 mL of PA6 / formic acid / BC solution into a 5 cm x 5 cm mold. Prepare a solution of 1.4 g of sodium carbonate dissolved in 18.6 mL of deionized water. Drop the solution into the mold at a rate of 1 drop per second using a syringe. Observe the generation of a large amount of CO2 bubbles. Let it stand for 3 h until it is completely solidified. Take out the foam and soak it in deionized water for 24 h to remove residual formic acid. Dry it at 60°C for 12 h to obtain PA6-BC foam.

[0047] Example 3:

[0048] The preparation method of a multi-layer interface evaporator is as follows:

[0049] Fix a 4 cm x 4 cm loofah on the spinning machine drum and spin it on the surface according to the method of Example 2 to obtain CL-PAN-PANI / Loofah; then, place it in the mold with the CL-PAN-PANI light-heat layer on top and the loofah connection layer on the bottom, pour the PA6-BC foaming solution prepared in Example 3 (cover to 1 / 3 of the bottom of the loofah), and add sodium carbonate solution to induce foaming. After the reaction is complete, take it out to obtain a light-heat layer (CL-PAN-PANI)-connection layer (loofah)-support layer (PA6-BC) integrated structure.

[0050] Comparative Example 1

[0051] The comparative example 1 provides a preparation method of pure PAN film without CL, as follows:

[0052] The specific operation method is the same as that of example 2, except that the PAN solution is directly spun to obtain a pure PAN film, which is then directly dried, and other parameters remain unchanged.

[0053] Comparative example 2

[0054] The comparative example 2 provides a preparation method of CL-PAN photothermal film without PANI, as follows:

[0055] The specific operation method is the same as that of example 2, except that the CL-PAN film is directly dried after being obtained, and polyaniline is no longer grown in situ, and other parameters remain unchanged.

[0056] Comparative examples 3-6

[0057] The comparative examples 3-6 provide preparation methods of PA6-BC foams with different BC contents, as follows:

[0058] The specific operation method is the same as that of example 3, except that the amount of BC added to the PA6 / formic acid solution is 0wt.%, 1wt.%, 2wt.% and 4wt.% respectively, and other parameters remain unchanged.

[0059] Test example 1

[0060] This test example analyzes the micro-morphology of examples 1 and comparative examples 1-2, and the results are shown in Figure 1 .

[0061] As shown in Figure 1 a-b, the PAN electrospun film presents a smooth, uniform and porous nanofiber structure. However, the addition of CL powder can change the concentration of the spinning solution, and partial aggregation phenomenon can easily occur during the spinning process. Therefore, in Figure 1 c-d, the electrospun film prepared by adding CL powder has aggregates of different sizes, and the CL powder is wrapped, twisted and contained in the entire fiber by the unspun polyacrylonitrile. Figure 1 c-d shows the morphology of the CL-PAN-PANI photothermal layer after in-situ growth of PANI on the CL-PAN base film. The nanofiber becomes rough, and it can be observed that PANI grows in a conical structure and covers the CL-PAN nanofiber. Since PANI also has photothermal conversion performance, the photothermal efficiency of the photothermal layer is improved. The synergistic effect of PANI and CL components makes the photothermal performance of CL-PAN-PANI significantly higher than that of CL-PAN photothermal film.

[0062] Test example 2

[0063] The test example will analyze the micro-morphology of Example 2 and Comparative Examples 3-6, and the results are shown in Figure 2

[0064] The PA6 foam without BC powder has rich and uniform internal micro-pore structure. The rich pore structure produced by the reaction of the sodium carbonate solution and the foaming solution helps the foam to transport water. After adding the BC powder, the BC particles are embedded in the internal micro-pores of the PA6-BC foam, and the surface of the BC particles is rough and can adsorb impurities in water. With the increase of the proportion of BC, the internal micro-pores of the foam are gradually covered by more BC particles, and some particles may agglomerate, which may cause the micro-pores to be blocked; secondly, the micro-pores produced by the foaming solution mixed with BC powder during the foaming process are also less uniform, which further leads to the decline of water transport performance. At a content of 3wt.% BC, the PA6-BC foam can have a higher dye adsorption efficiency under the premise of having a higher stable water transport.

[0065] Test Example 3

[0066] In this test example, salt deposition tests will be performed on Example 1, Example 3, and Comparative Example 2, and the results are shown in Figure 3

[0067] In order to further study the change of evaporation performance related to salt deposition under long-term infrared irradiation, the salt deposition phenomenon on the surface of the nanofiber membrane of CL-PAN, CL-PAN-PANI and multi-layer solar interface evaporator was observed every 1 hour under the condition of 1 solar irradiation intensity for 5 hours in 3.5wt.% NaCl solution, and was recorded by taking pictures. As shown in Figure 3 ​​As shown, no obvious NaCl deposition occurred on the surface of the CL-PANI film of Comparative Example 2 and the CL-PAN-PANI film of Example 1 within the first hour of irradiation, but as the irradiation time increased, a small amount of NaCl deposition began to occur on the surface of the CL-PAN-PANI film of Example 1. This is because the CL-PAN-PANI film with in-situ grown PANI has a higher light-heat conversion capability than the CL-PAN film. Under the condition that the water flow rate is substantially the same, the light-heat layer with a higher light-heat conversion efficiency evaporates more water in a unit of time, and after the water in the saltwater solution evaporates, the salt particles are deposited on the surface of the film. After 5 hours of irradiation, a small amount of NaCl deposition occurred on the surface of the CL-PAN film, while the CL-PAN-PANI film had a higher amount of NaCl deposition on its surface due to the highest evaporation rate. However, compared to Example 1, a large amount of salt did not come out of the surface of the multilayer interfacial evaporator in Example 3, and as the time extended, the degree of local aggregation of salt particles was lower than that of the single-layer interfacial evaporator. Unlike the single-layer interfacial evaporator with only the CL-PAN-PANI light-heat film, the multilayer structure additionally comprises a foam support layer and a loofah adapter layer, which preliminarily filters the saltwater, avoids direct contact between the light-heat layer and the saltwater, and reduces the deposition of salt particles on the surface of the light-heat layer. This result further indicates that the multilayer structure evaporator improves the salt resistance while maintaining the evaporation performance of the light-heat layer CL-PAN-PANI, ensuring the stable evaporation of water.

[0068] Test Example 4

[0069] In this test example, water evaporation tests were performed on Example 3 to characterize the evaporation rate of the composite fiber film, as shown in Figure 4 .

[0070] The solar-driven interfacial evaporation performance of Example 3 was evaluated under the irradiation of sunlight. As can be seen from Figure 4 , whether in pure water or in saltwater, the highest water evaporation rate was 1.799 kg m -2 h -1 and 1.675 kg m -2 h -1 , respectively; and in ten cycles of pure water and saltwater evaporation tests, the average evaporation rate was 1.772 kg m -2 h -1 and 1.679 kg m - 2 h -1 , indicating that the multilayer solar interfacial evaporator has good interfacial evaporation stability.

[0071] Test Example 5

[0072] In this test example, dye adsorption tests were performed on Example 2 and Comparative Examples 3-6, as shown in Figure 5 .

[0073] The methylene blue (MB) solution was used as a typical organic dye pollutant to evaluate the dye adsorption performance of the support layer.

[0074] Table 1 Adsorption rate of different BC content of foam support layer to methylene blue dye

[0075]

[0076] As can be seen from Table 1, with the increase of adsorption time, the adsorption rate of the support layer to MB gradually increases, wherein the adsorption rate of Example 2 can reach 96.9% after 48h of adsorption, so that the prepared solar interface evaporator has the potential to be applied to industrial dye wastewater treatment.

[0077] The above description of disclosed embodiments enables one of ordinary skill in the art to make or use the application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the generic principles defined herein can be applied to other embodiments without departing from the spirit or scope of the application. Thus, the present application is not intended to be limited to the embodiments shown herein but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A multi-layer solar interface evaporator, characterized in that: The multilayer solar interface evaporator is composed of a photothermal layer, a connecting layer and a support layer connected in sequence from top to bottom: carbonized loofah is ground and sieved, then combined with the polymer material polyacrylonitrile, and then blended on the surface of the loofah with the help of electrospinning technology to obtain a composite fiber membrane; polyaniline is then in situ grown on the surface of the composite fiber membrane to prepare a modified photothermal layer; finally, a foam support layer is prepared at the bottom of the connecting layer using solution foaming technology to obtain a biomass-based multilayer solar interface evaporator based on loofah.

2. A method for preparing a multilayer solar interface evaporator according to claim 1, characterized in that: The method specifically comprises the following steps: (1) Fixing the connecting layer: Bind the loofah connecting layer to the electrospinning machine receiver; (2) Preparation of spinning solution: Carbonized loofah, polyacrylonitrile powder and N,N-dimethylformamide are uniformly stirred in a certain proportion to obtain a spinning solution; (3) Preparation of the photothermal layer: The spinning solution is loaded into a syringe and placed in the push pump position of the electrospinning machine, and a carbonized loofah-polyacrylonitrile fiber membrane is spun on the loofah connecting layer using electrospinning technology; then polyaniline is in situ grown on the membrane to obtain a carbonized loofah-polyacrylonitrile-polyaniline photothermal layer; (4) Preparation of the support layer: A foaming solution was prepared using polyamide 6, commercial bamboo charcoal powder and formic acid solution, and in-situ foaming was performed on the bottom of the loofah connecting layer to obtain the support layer.

3. The method for preparing a multilayer solar interface evaporator according to claim 2, characterized in that: In step (2), the preparation method of the photothermal layer includes: dissolving carbonized loofah powder and polyacrylonitrile powder in N,N-dimethylformamide in a mass ratio of 1:1, wherein the polyacrylonitrile concentration is 10wt%, stirring and then ultrasonically dispersing to obtain a uniformly dispersed spinning solution for preparing the CL-PAN fiber membrane.

4. The method for preparing a multilayer solar interface evaporator according to claim 2, characterized in that: In step (4), the support layer is prepared as follows: the photothermal layer attached to the surface of the loofah connecting layer prepared in step (2) is cut to be slightly smaller than the mold, and is placed into the mold with the photothermal layer facing upward and the connecting layer facing downward; then the prepared sodium carbonate solution is slowly and uniformly dripped from the edge into the polyamide 6 / formic acid mixed solution; after the Na2CO3 solution is injected, it is allowed to stand and foam, and when CO2 is no longer generated, it indicates that the foam support layer has been prepared.

5. Use of the multilayer solar interface evaporator according to claim 1 or the multilayer solar interface evaporator prepared by the preparation method according to any one of claims 2 to 4 in seawater desalination and industrial wastewater treatment.

Citation Information

Patent Citations

  • Interface evaporation device with porous hydrophobic / hydrophilic structure and preparation method of interface evaporation device

    CN115124101A

  • Preparation method of modified luffa stem steam generator and modified luffa stem-based seawater desalination evaporator

    CN115745055A

  • Solar interface evaporation device and preparation method and application thereof

    CN117647019A

  • Carbonized loofah photo-thermal evaporator with city wall structure and preparation method and application of carbonized loofah photo-thermal evaporator

    CN117699893A

  • Solar-driven interface water evaporation and photocatalytic dye degradation dual-functionalized composite fiber membrane as well as preparation method and application thereof

    CN118007318A

Cited By

  • Self-floating type double-layer solar evaporator with Janus characteristic and preparation method and application of self-floating type double-layer solar evaporator

    CN121159932A